Do processamento auditivo em militares expostos a elevados níveis de pressão sonora - Marins, Karynne Kelly Rezende Carvalho (2004)
The lingering exposition at excessive noises can to cause in the individual hearing loss and simultaneously, difficulty in oral communication. The objective of this research is to show the behavior of the auditory processing in militaries with and without hearing loss, exposed at high levels of the sound pressure. The sample constituted of 57 mail sex individual, with age between 28 and 52 years old, exposed at airship noises, being 24 of the without hearing loss group (A), and 33 of the with hearing loss group (B). The individuals were submitted at anamnesis, basic auditory evaluation, Filtered Speeching test, SSW test and Frequency Pattern test. Had been used the Kruskal-Wallis and Wilcoxon non-parametrics statistics tests for analysis the results, considering as significant the p value < 0,05. The results allowed to concluse that the exhibition at high levels of the sound pressure have deleterious effects in auditory processing of the militaries, independent of the presence our no the audition outlying alteration.